Effect of Different Housing System on the Morphological Traits, Physiological Responses and Behavioral Observations of Sirohi Kids - Waiz, H. A.; Gautam, L. (International Journal of Bio-resource and Stress Management, 2021)
The research was carried out at the Instructional Livestock Farm, College of Veterinary and Animal Sciences, Udaipur (RAJUVAS), Rajasthan, India during September to December, 2021 to determine how the conventional and loose housing systems affect the morphological characteristics, physiological reactions, and behavior of Sirohi goat kids. A total of twenty-four Sirohi goat kids were randomly allocated into two groups, with twelve goats in each group, housed in a loose housing system and a conventional housing system. The research revealed a notable distinction in morphological characteristics like body length, height at wither, and heart circumference between the two different housing systems. Heart girth, height at withers, and body length were observed to be more advanced and prominent in the loose housing system in contrast to the conventional housing system as age progressed. Nevertheless, there was no significant variance observed in the physiological parameters such as pulse rate, respiration rate, and rectal temperature among the two housing categories. Moreover, the conventional housing system exhibited considerably (p<0.05) higher observable behavioral responses, including feeding, drinking, ruminating, and butting, in comparison to the loose housing system. The study’s findings indicated that goats housed in the loose housing system at Institution Livestock Farm, College of Veterinary and Animal Science, Udaipur, yielded greater benefits in terms of financial returns, performance, and behavioral responses.